2010
DOI: 10.1371/journal.ppat.1000911
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidis Opc Invasin Binds to the Sulphated Tyrosines of Activated Vitronectin to Attach to and Invade Human Brain Endothelial Cells

Abstract: The host vasculature is believed to constitute the principal route of dissemination of Neisseria meningitidis (Nm) throughout the body, resulting in septicaemia and meningitis in susceptible humans. In vitro, the Nm outer membrane protein Opc can enhance cellular entry and exit, utilising serum factors to anchor to endothelial integrins; but the mechanisms of binding to serum factors are poorly characterised. This study demonstrates that Nm Opc expressed in acapsulate as well as capsulate bacteria can increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 66 publications
(163 reference statements)
3
82
0
Order By: Relevance
“…Most pathogenic bacteria bind VN at either its N-terminal region (37), its central domain (containing HPX-like domains) (30), or the basic carboxy-terminal HBD-3 (38). Usually, bacterium-VN binding does not interfere with the VN domain involved in the inhibition of the C5b9 complex, thus allowing this complement regulator to remain active in inhibiting MAC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most pathogenic bacteria bind VN at either its N-terminal region (37), its central domain (containing HPX-like domains) (30), or the basic carboxy-terminal HBD-3 (38). Usually, bacterium-VN binding does not interfere with the VN domain involved in the inhibition of the C5b9 complex, thus allowing this complement regulator to remain active in inhibiting MAC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Like OmpU, OMPs of intracellular pathogens can mediate adherence to host cells, stimulating host transduction pathways required for bacterial entry. One remarkable example is that of OpC from Neisseria meningitidis, which binds to human serum factors like activated vitronectin and to a lesser extent fibronectin to attach to and invade human brain endothelial cells (11). In these cells, fibronectin/ vitronectin serve as molecular bridges between the pathogen and the host RGD-recognizing αvβ3-integrin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…As bacterial surface components, OMPs are both used by hosts for pathogen recognition and by pathogens for interaction with and invasion of host cells, serving as adhesion proteins (adhesins) (7)(8)(9) or invasion proteins (invasins) (10,11). OmpU is a major porin from the Vibrio species.…”
mentioning
confidence: 99%
“…Furthermore, the use of Opc-deficient mutant strains demonstrated that JNK signaling, but not p38 signaling, was mediated by Opc expression (192). A more recent study identified that Opc preferentially binds to activated vitronectin within human serum and that this interaction promotes N. meningitidis invasion of HBMECs (155). In vitro, the enhanced invasion of nonencapsulated N. meningitidis strains is thought to be due to the unmasking of Opc; however, the role of Opc in vivo has yet to be determined.…”
Section: Bacterial Mechanisms Of Brain Invasionmentioning
confidence: 99%